A comparison of gamma and neutron irradiation on Raji cells: effects on DNA damage, repair, cell cycle distribution and lethality - Mustonen, Riitta; Bartsch, Helmut (Mutation research. Fundamental and molecular mechanisms of mutagenesis, 1999)
The Comet assay (microgel electrophoresis) was used to study DNA damage in Raji cells, a B-lymphoblastoid cell line, after treatment with different doses of neutrons (0.5 to 16 Gy) or gamma rays (1.4 to 44.8 Gy). A better growth recovery was observed in cells after gamma-ray treatments compared with neutron treatments. The relative biological effectiveness (RBE) of neutron in cell killing was determined to be 2.5. Initially, the number of damaged cells per unit dose was approximately the same after neutron and gamma-ray irradiation. One hour after treatment, however, the number of normal cells per unit dose was much lower for neutrons than for gamma rays, suggesting a more efficient initial repair for gamma rays. Twenty-four hours after treatment, the numbers of damaged cells per unit dose of neutrons or gamma rays were again at comparable level. Cell cycle kinetic studies showed a strong G2/M arrest at equivalent unit dose (neutrons up to 8 Gy; gamma rays up to 5.6 Gy), suggesting a period in cell cycle for DNA repair. However, only cells treated with low doses (up to 2 Gy) seemed to be capable of returning into normal cell cycle within 4 days. For the highest dose of neutrons, decline in the number of normal cells seen at already 3 days after treatment was deeper compared with equivalent unit doses of gamma rays. Our present results support different mechanisms of action by these two irradiations and suggest the generation of locally multiply damaged sites (LMDS) for high linear energy transfer (LET) radiation which are known to be repaired at lower efficiency.
Gesehen am 02.02.2021